2020
DOI: 10.21203/rs.3.rs-23953/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unique Immunological Profile In Patients With COVID-19

Abstract: The relationship between SARS-CoV-2 and host immunity is unknown. We show here that patients with COVID-19 had an altered immune phenotype, with an expansion of adaptive FceRIgneg NK cells, and inflammatory CD14+CD16+ monocytes. T cells were reduced and overexpressed the Tim-3 exhaustion molecule. Low frequencies of CD8 T cells and NKG2A+ NK cells, and expansion of mature CD57+ NK cells were associated with poor prognosis. These findings unveil a unique immunological profile in COVID-19 patients.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 11 publications
6
62
0
Order By: Relevance
“…Studies from other coronaviruses suggest that type 1 immunity is the primary mechanism controlling the infection (Janice Oh et al, 2012;Shin et al, 2019). In severe COVID-19, blood CD4 + T, CD8 + T and NK cells expressed markers of exhaustion (Varchetta et al, 2020), a finding not mirrored in moderately sick Syrian hamsters. In contrast, T and NK responses were effective and self-resolving.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other coronaviruses suggest that type 1 immunity is the primary mechanism controlling the infection (Janice Oh et al, 2012;Shin et al, 2019). In severe COVID-19, blood CD4 + T, CD8 + T and NK cells expressed markers of exhaustion (Varchetta et al, 2020), a finding not mirrored in moderately sick Syrian hamsters. In contrast, T and NK responses were effective and self-resolving.…”
Section: Discussionmentioning
confidence: 99%
“…They still, however, claim their findings suggest that T-cell activation and exhaustion play a role in Covid-19 and posit T-cell targeted treatment options may be of interest ( 16 ). Varchetta et al report an increase in TIM-3 and CD69 expression in CD8+ T cells and note the extent of CD8+ T cell lymphopenia was significantly greater in patients that succumbed to Covid-19 ( 17 ). They describe this as a hyperactivated/exhausted state and observed that during recovery TIM-3 and CD69 expression on T cells fell and CD8+ lymphocyte count rose.…”
Section: Discussionmentioning
confidence: 99%
“…54 A recent study also pointed out that NK cells from patients with coronavirus disease 2019 (COVID-19) downregulate NKG2D; although this study did not investigate MICA/B shedding, soluble MICA/B proteins are frequently linked to NKG2D downregulation, and thereby, COVID-19 patients may have higher levels of soluble MICA/B shed in their blood circulations. 55 Taken together, MICA/B shedding is a conserved mechanism of immune escape that is also relevant to viral infections, and thus, the inhibition of MICA/B shedding may confer a significant benefit for patients infected with viruses such as HIV, HBV, HCMV and coronavirus.…”
Section: Virally Infected Cells Express and Shed Mica/bmentioning
confidence: 99%